Regulation and Technical Change: Some Largely Unexplored Influences - Eads, George C. (American Economic Review, 2016)
Regulation is likely to change both the level and direction of innovative activity in this country, but our knowledge both of regulation and of the innovation process is too primitive for us to tell precisely what these changes will be. Rather than make major changes in the regulatory process on the grounds that they will aid innovation, we are better advised to confine our attention to improving the general climate for innovation and altering those aspects of regulation that even casual investigation may suggest be deleterious. That, is the direction suggested by most recent important studies; their degree of caution is appropriate. 5 references.